Omega-3 Supplementation is Effective in Reducing Interleukin-6 Levels After Physical Exercise: A Systematic Review - Ayubi, Novadri; Wibawa, Junian Cahyanto; Aljunaid, Mohammed; Lobo, Joseph; Callixte, Cyuzuzo; Lesmana, Heru Syarli (AL-Kindy College Medical Journal, 2025)
Not only does physical exercise improve health, it can also trigger inflammation. Therefore, supplementation after exercise is necessary to reduce it. Omega 3 is one of the nutrients that can potentially reduce inflammation. The fundamental however, the mechanism is not well known. This study examined how omega-3 supplementation while exercise affected IL-6 levels, an inflammatory biomarker. Our systematic review analysis examined interleukin 6, inflammation, and omega 3 papers from Pubmed, Web of Science, and Science Direct during the previous five years. This systematic review assessed nine eligible papers. This research assessed standard operating procedures using PRISMA. Taking omega-3 supplements while working out has been shown to reduce IL-6 levels. IL-6 is reduced by omega-3 supplementation during exercise. So, this can be a recommendation for sportsmen in routine consumption to prevent inflammation during exercise.